HUBUNGAN PEKERJAAN IBU DAN DUKUNGAN SUAMI TERHADAP KEGAGALAN IBU DALAM MEMBERIKAN ASI EKSKLUSIF DI PUSKESMAS RAMBAH SAMO I - Yuyun Bewelli Fahmi; Herma Yesti (Fakultas Ilmu Kesehatan, 2021)
The main source of nutrition needed for a baby aged less than 6 months is breast milk. Breast milk has many benefits because it is a food that contains balanced nutrition for babies, and contains immune substances that can reduce the risk of the baby contracting disease. The importance of exclusive breastfeeding for babies will greatly impact the development of the child. The failure of exclusive breastfeeding is influenced by internal factors (mother's work and husband's support) and external factors (promotion of infant formula, birth attendants). This type of research is quantitative with an analytic approach, with a cross sectional design. This population was all mothers who had babies over 6 months at the time of the study. The sampling technique was purposive sampling, amounting to 130 people. Data analysis used statistical test with chi square. Based on the results of the study, it was found that there was no relationship between maternal work and the failure of mothers to provide exclusive breastfeeding, the results obtained from the chi square test p> 0.005 (p = 0.65), there was a relationship between husband's support and the failure of mothers to provide exclusive breastfeeding, the value of p> was obtained. 0.05 (p = 0.45). After doing this research, the work and support of the husband is very important for the achievement of exclusive breastfeeding, thus it is hoped that health workers will always improve the quality of health services by providing information about the importance of giving exclusive breastfeeding to their babies until they reach age. 6 months.